Design of a Semi-Submersible Tourism Ship for Bunaken Underwater Recreation in Manado, Indonesia - Wasis Dwi Aryawan; M Hafiz Nurwahyu Aliffrananda; Danu Utama; Hasanudin Hasanudin; Yuda Apri Hermawan (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
With a rapid increase in various number of marine tourism destinations, especially in The Bunaken National Park with the amount of tourists that has increased throughout the year rising by 23% for domestic tourists and 12% for international tourists between 2002 and 2018. Unfortunately, to enjoy the underwater scenery of The Bunaken National Park can access by diving and snorkeling which is not all tourist can do that. Furthermore, in order to support the marine tourism industry in Indonesia, a semi-submersible tourism ship was developed with a glass at the hull's bottom based on the standard spiral design and the safety standard established by the rules so the tourists can easily enjoy the underwater ecosystem. The concept design of bottom-glass ship with trimaran hull type is offered as a problem-solving in this paper. The final design of the main dimensions are length of overall (LOA): 23,1 meters, width (B): 8 meters, Draft (T): 2.22 meters but the maximum submerged up to 2,5 meters, speed of 10 knots, and passenger capacity of 44 persons.